Political communication in the age of social media - Munardin Hadma, Ahmad; Dwi Anggoro, Juliardi (Universitas Ahmad Dahlan, 2022)
The development of communication technology has penetrated human life. One form of communication technology development is new media (new media) which then gave birth to social media. The world of politics cannot be separated from the influence of the development of new media and social media. Social media are like two sides of a coin for political actors. On the one hand, the success of using social media can enable political actors to get positive support. But on the other hand, failure to take advantage of social media risks damaging the image he has. This article uses a qualitative approach to discuss the challenges and opportunities of social media for political actors. The explanation of the use of social media in political communication is the first part of this paper. The second part discusses the challenges faced by political actors in this 4.0 era The third part offers an opportunity for political actors to use social media. The fourth or final part is a conclusion that contains what political actors should do to minimize risks and maximize the opportunities offered by social media.